Range extension of Isthmoheros tuyrensis, a threatened species of fish (Cichlidae) in Panama: including new ecological and morphological data - Dominici Arosemena, Arturo (2023)
There are two endemic species of Cichlidae in southern Central America, both found in the Pacific Slope of Eastern Panama (PSEP). One is Isthmoheros tuyrensis, which until now was presumed to be distributed in the Darien Province and the Bayano River basin. Information on distribution and ecology of I. tuyrensis is relatively scarce. In this investigation we report a new range extension for the species and provide additional morphological and ecological data. Fish were sampled using electrofishing and cast nets, in three river basins of the Panama District (Matasnillo, Juan Díaz, and Pacora) from August–September (rainy season) of 2020, February–March (dry season), and April (transition season) of 2021. Fish diversity, water quality, and physical parameters were gathered within the upper, middle, and lower portions of the three basins. This study focused on the localities where specimens of I. tuyrensis were found (i.e., Pacora river basin). The presence of the species in localities with significant anthropogenic threats results in a potential barrier for distribution, along with the possibility of extirpation due to heavy pollution – in particular from the rivers on the western side of Panama City. In addition, we note an increase in urban threat from the east of the city due to expanded development and agricultural activities. I. tuyrensis, the virtually unknown “Aveinte” in Spanish or the “Isthmian Hero”, is listed as Vulnerable by the International Union for Conservation of Nature (IUCN)’s Red List and inhabits some river basins lacking effective protection, being the only endemic fish species located in an urban basin in the Pacific of Mesoamerica. The information on distribution, morphology, and ecology provided here will contribute to a better understanding of the species’ biology and will aid the creation and implementation of management and conservation measures